A Study on Truck Dispatching in Open Pit Mines: Improving Efficiency and Optimization in Truck Dispatching in Open Pit Mines (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Mines are dynamic systems, each truck's cycle travel time is short relative to the duration of the shift and often the timing requirements are high at each loading point. For simulation systems, the idea of real-time truck dispatching techniques was used. This model's fundamental definition for truck allocation is developed based on three unknown parameters truck cycle time, matched truck and shovel loading time, and truck and shovel inactive periods. The stochasticity is represented by inherent problem uncertainties, that are represented in most real-world problems classical and deterministic approaches does not consider uncertain behavior of real-world problems, leading most of time to non-optimal results. Truck dispatching problems in open-pit mines are often subject to uncertain behavior, such as fuel consumption variations, unexpected equipment stopping (faults, at tires, emergencies, etc.), and time variations of durative actions. Therefore, the truck dispatching modeling by a stochastic approach becomes crucial in order to attend and optimize its special objectives. We also present additional techniques for truck dispatching that are used in further analysis, namely greedy heuristic, MTCT (Minimizing Truck Cycle Time) heuristic, and GAs.